Breeding and dispersal implications for the conservation of the Southern Ground Hornbill Bucorvus leadbeateri - Carstens, Kate (Percy FitzPatrick Institute of African Ornithology, 2018)
Populations of secondary tree-cavity nesting bird species are often limited by a shortage of natural nesting sites. For the Southern Ground Hornbill Bucorvus leadbeateri that typically nests in natural tree cavities, the shortage of nesting sites is one factor potentially limiting population growth. The species is listed as endangered in South Africa, and vulnerable throughout the rest of its range. Nest boxes can improve the conservation status of threatened birds that are limited by nest-site availability. However, nest boxes or other types of artificial nests are not always beneficial to the target species, and their value as a conservation tool needs to be tested for each species. Wooden nest boxes were installed for ground hornbills in a study area in north eastern South Africa with a paucity of natural nest sites. In this thesis, I assess productivity, timing of breeding, and dispersal in the Southern Ground Hornbill in a study area supplemented with nest boxes and discuss the implications for the conservation of this endangered species. Nest boxes are an effective conservation tool to improve productivity in areas lacking natural tree cavity nesting sites. Breeding success (calculated as the proportion of nesting attempts that fledged a chick) and predation levels were similar for groups using nest boxes and natural nests. Natural nests were more buffered against cooling night temperatures, but otherwise nest boxes provided nesting conditions that were no better than natural nests. Timing of breeding for nests in natural tree cavities and nest boxes were similar. However, groups with access to a nest box attempted breeding more often than groups with access to a natural nest only, resulting in an 15 % increase in the number of fledglings per group compared to an adjacent protected area with no artificial nests. The number of breeding groups in the study area increased by 460 % over 12 years. However, there is a limit to the density of breeding groups. Breeding success was highest when breeding density was one breeding group per 90-120 km², so nests should be spaced ~10 km apart. Given that the threats to ground hornbills include persecution and poisoning, increasing the reproductive rate by providing nest boxes should assist in slowing the decline by the increased recruitment of offspring into the population. Timing of breeding varied across years. The first eggs laid each year ranged from 9 September to 14 November, and median lay date was 03 November. Breeding attempts that were initiated early in the season were more likely to fledge a chick than those initiated later in the season. Timing of breeding was delayed during warmer springs, particularly under dry conditions. In savannas, hotter spring temperatures could limit food availability, for example, if higher temperatures cause the vegetation to dry out, resulting in a rapid decline in insect flush, especially in the phytophagous insect groups that form a large part of the ground hornbill diet. Factors to consider when constructing and placing nest boxes include thickness of the cavity walls, entrance height above ground and density of nest boxes placed in the landscape. Breeding attempts in natural nests and nest boxes with thicker nest walls and those positioned with higher entrances above the ground increased breeding success. Therefore, nests should be constructed with cavity walls at least 6 cm thick and placed so that the entrances are situated > 6 m above the ground. With 186 ringed chicks fledging from the study area after the installation of nest boxes, it was possible to observe their dispersal within the study area and farther away into the adjacent Kruger National Park. There was no evidence for sex-biased dispersal. Males and females dispersed at similar ages, and over similar distances, raising interesting questions about inbreeding avoidance mechanisms in this species. If females do not disperse beyond the range of related males, how do related individuals avoid pairing, and what forms of individual recognition exist?